An overview of thioacetamide-induced hepatotoxicity. (11th June 2013) - Akhtar, Tasleem; Sheikh, Nadeem
Abstract: Thioacetamide (C2 H5 NS; TAA), an organosulfur compound is formally used in leather processing, laboratories, textile and paper industries. TAA is a model hepatotoxicant, consumed to induce acute and chronic liver injury due to its effects on protein synthesis, RNA, DNA and Gamma-glutamyl transpeptidase activity. TAA undergoes a two-step bioactivation to sulfine, and afterward to sulfene, a reactive metabolite. Sulfine is accountable for the enlargement of nucleoli, increase in nuclear volume and intracellular concentration of Ca ++, change in cell permeability, and inhibit mitochondrial activity. At the same time Sulfene is responsible for the release of nitric oxide synthase and NF-jB directing to centrilobular necrosis, protein denaturation and lipid peroxidation. Furthermore, it impairs the urea cycle and the activity of ornithine aminotransferase. Prolonged oral intake of this compound directs to macro liver nodules, liver cell adenomas, cholangiomas and hepatocarcinomas, histologically similar to that caused due to viral hepatitis infection.